(untitled) (Praxis Educativa, 2026)
This essay aims to reflect on the importance of collaborative work in rural intercultural schools within the Chilean educational system, focusing on the subjects of Indigenous Language and Physical Education. Rural intercultural schools are conceived as spaces that promote an education based on the recognition of cultural differences and equitable treatment, in coherence with the territorial context. Within this framework, interculturality is manifested in the cultural diversity of the rural classroom and the surrounding territory, becoming an essential element for addressing themes rooted in the local context. From this perspective, subjects such as Indigenous Language and Physical Education foster collaborative and interdisciplinary work through shared content, such as traditional games and Palín, addressed in both their theoretical and practical dimensions, thereby contributing to deep learning. Nevertheless, challenges persist, particularly related to the lack of leadership support and limited ongoing professional development to strengthen these collaborative practices.